Social Construction of Covid-19 Vaccination and its Implications on Achieving Herd Immunity in Indonesia - Febrianto Syam (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This article aims to highlight potential challenges to achieving herd immunity in Indonesia through the COVID-19 vaccination program. A key aspect of this article is the influence of social constructs on the COVID-19 vaccine, which impact compliance and participation rates. This article demonstrates the reality of negative social constructs on COVID-19 vaccination developing in Indonesian society. This poses a significant challenge that requires serious attention. Negative social constructs on vaccines appear to pose a serious threat to ensuring herd immunity as a pandemic control strategy. This situation appears to be related to the formation of public perceptions, which tend not to be fully controlled by the government